TPP crosslinking influence on the effect of sprayed dried microparticles based on industry waste sourced-chitosan over crop pathogens - Florencia Anabel Mesas; Merari Tumin Chevalier; Julieta Renée Mendieta; María Cecilia Terrile; Pablo Villanueva; Claudia Anahi Casalongué; Vera Alejandra Álvarez; Alberto Antonio Chevalier; Sergio Martin-Saldaña (Next Sustainability)
The use of fishing industry waste residues for biotechnological developments is blossoming in the last decade to improve the management of marine resources while reducing the environmental impact of the fisheries sector. Chitosan (CS), is a natural and nontoxic biopolymer that exerts great antimicrobial properties and is being considered as GRAS by the United States Food and Drug Administration. In this study, we aimed to produce at a gram scale high molecular weight CS microparticles (CS-MP) from a low quality commercial raw material intended to develop an environmental friendly antimicrobial. Thus, we aimed to test the effect of sodium tripolyphosphate (TPP) used as a crosslinker on the antimicrobial performance of the CS-MP. Hence, we synthesized CS using shrimp fishing industry waste from Argentinean Patagonia at a pilot scale in order to be able to provide a cost-effective second life to the industry waste. By varying the ratio polymer/crosslinker, we studied its influence on the final physicochemical properties as well as their performance against representative crop pathogens: Pseudomonas syringae pv. tomato DC 3000 and Fusarium solani f. sp. eumartii. Our results showed a correlation between the surface charge exhibited by CS-MPs and their antimicrobial properties, through an imbalance on fungal membrane permeability. Thus, given the difference in the CS-MPs performance, it is clear that the electrostatic interaction of the particles with the negatively charged surface of the microorganism plays a key role in determining their ultimate activity. The CS-MPs exhibited great potential against crop pathogens providing a second life to fishing industry waste by developing an eco-friendly plant protectant from a valuable synergy of the national industry and academics.